Dietary 25-hydroxycholecalciferol modulates gut microbiota and improves the growth, meat quality, and antioxidant status of growing-finishing pigs - Zhang, Lianhua; Long, Shenfei; Wang, Hongliang; Piao, Xiangshu (Frontiers in Microbiology, 2023)
25-hydroxycholecalciferol (25OHD3) is the active metabolite of regular vitamin D3 in vivo, which has a stronger biological activity and is more easily absorbed by the intestine than regular vitamin D3. Our study aimed to detect the potential influences of 25OHD3 on pork quality, antioxidant status and intestinal microbiota of growing-finishing pigs receiving low-phosphorus (P) diet. Forty pigs [initial body weight (BW): 49.42 ± 4.01 kg] were allocated into two groups including low-P diet (CON group) and low-P diet supplemented with 50 μg/kg 25OHD3 (25OHD3 group). The results showed that 25OHD3 supplementation tended to FCR in phase 3 and overall phase in comparison with the CON group. On d 88, 25OHD3 improved (P < 0.05) serum contents of SOD and GSH-Px and reduced (P < 0.05) serum BALP level. 25OHD3 increased (P < 0.05) mucosal GSH-Px activity in the duodenum and ileum, and tended to increase a* value and the activities of T-AOC and SOD in the longissimus dorsi muscle. 25OHD3 significantly upregulated the mRNA level of Cu/Zn SOD, and tended to change the mRNA levels of Nrf2 and Keap1 in the longissimus dorsi muscle. Moreover, 25OHD3 supplementation decreased (P < 0.05) n-6/n-3 PUFA and iodine value in the longissimus dorsi muscle. For bone quality, 25OHD3 supplementation increased (P < 0.05) Ca content, BMC and breaking strength in the metacarpal bones. Moreover, the colonic abundance of Lactobacillus was significantly higher in pigs fed with 25OHD3, and exhibited a positive association with serum antioxidant status, pork quality and bone characteristics. Overall, the inclusion of 25OHD3 in low P diet partly improved production performance, meat quality, antioxidant capacity, bone properties and gut microbiota composition of growing-finishing pigs.